Normative analysis of the legal status of Catholic church annulment in the national legal system: A comparison of the concepts of annulment and divorce - Wicaksono, Emirza Nur (Priviet Social Sciences Journal, 2026)
This study normatively analyzes the legal status of the Catholic Church’s annulment within the Indonesian national legal system by comparing the concepts of annulment and divorce. This study is normative legal research that employs statutory and conceptual approaches. The results indicate that annulment in Catholic Church Law is declarative and based on the principle of the indissolubility of marriage, thus being conceptually distinct from divorce in national law. Although annulment shares similarities with marriage annulment, the decisions of ecclesiastical tribunals do not have binding legal force in the national legal system because they are not explicitly regulated by Law Number 1 of 1974 concerning Marriage. This lack of synchronization between canon and national laws creates legal uncertainty and has implications for the protection of Catholic citizens’ rights. This research affirms the necessity of harmonizing legal norms within the framework of legal pluralism to achieve legal certainty and justice in the regulation of marital status in Indonesia